Primary Sclerosing Cholangitis Current Understanding, Management, and Future Developments - Forman, Lisa M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides a state-of-the art review of primary sclerosing cholangitis (PSC). The volume focuses on new data about the risk factors for PSC, its natural history of the disease, and the epidemiology and genetics of PSC, while providing a comprehensive overview on current and future therapies for PSC, management of cholangiocarcinoma, and other hepatobiliary malignancies. It also touches upon up-to-date surgical and endoscopic management, including liver transplantation-both deceased donor and living related liver transplantation. Written by experts in the field, Primary Sclerosing Cholangitis: Current Understanding, Management, and Future Developments is a valuable resource for clinicians, surgeons and researchers with an interest in biliary liver disease, inflammatory bowel disease, and liver transplantation.
Epidemiology and Natural History of Primary Sclerosing Cholangitis -- Malignancy and Primary Sclerosing Cholangitis: Cholangiocarcinoma, Hepatocellular Carcinoma and Gallbladder Carcinoma -- Primary Sclerosing Cholangitis-Associated Inflammatory Bowel Disease -- Overlap Syndromes of Primary Sclerosing Cholangitis -- IgG4-Related Sclerosing Cholangitis -- Pediatric Primary Sclerosing Cholangitis -- Cholangiocyte Biology -- Genetics of Primary Sclerosing Cholangitis -- Immunology of Primary Sclerosing Cholangitis -- Pruritus in Primary Sclerosing Cholangitis: New Insights into Cause and Treatment -- Ursodeoxycholic Acid Treatment in Primary Sclerosing Cholangitis -- Future Therapies for Primary Sclerosing Cholangitis -- Noninvasive Imaging of Primary Sclerosing Cholangitis: A Radiologic Perspective -- Endoscopic Evaluation and Management of Primary Sclerosing Cholangitis -- Percutaneous Biliary Intervention in Patients with Primary Sclerosing Cholangitis -- Liver Transplantation for Primary Sclerosing Cholangitis -- Recurrent Primary Sclerosing Cholangitis after Liver Transplantation. .
Keywords: Medicine; Gastroenterology; Hepatology; Medicine & Public Health; Gastroenterology; Hepatology